Forest conservation and well-being outcomes of a REDD+ initiative: A quasi-experimental assessment among smallholders in the Brazilian Amazon - Carrilho, Cauê Dias (2021)
REDD+ impact evaluations indicate deforestation is commonly reduced, despite null outcomes on well-being. However, as those evaluations are still rare, the effectiveness of REDD+ initiatives remain an open question. Even less studied is if outcomes achieved are sustained after initiatives end. Because most initiatives were evaluated shortly after the application of incentives, there is a knowledge gap about their long-term effects. Therefore, the main goal of this thesis was to assess both short and long-term effects of a Brazilian Amazon REDD+ initiative on deforestation and local peoples well-being. We also wanted to identify which were the driving factors behind the observed outcomes. We scrutinized the Projeto Assentamentos Sustentáveis na Amazônia, a REDD+ project implemented by a Brazilian NGO Instituto de Pesquisa Ambiental da Amazônia (IPAM) in the Transamazon highway region of the Pará state (Brazil). The initiative combined Payments for Environmental Services (PES) with sustainable livelihood alternatives to reduce smallholder deforestation. In the three chapters presented here, quasi-experimental designs were adopted. Data came from face-to-face surveys in a three-datapoint panel design. The purpose of the first chapter was to assess the effects of the REDD+ initiative on deforestation and perceived well-being, including intra-community spillover effects, besides scrutinizing to what extent the observed outcomes persisted after the initiative ended. Results indicate an average of 7.80% to 10.32% of forest cover was saved by the REDD+ initiative probably by providing PES. It also increased the probability of improving enrollees wellbeing by 27-44%. We found no evidence for significant intra-community spillover. After the initiative ended, forest loss rebounded and perceived wellbeing declined yet, importantly, past saved forest was not cleared. In the second chapter, we revisited the long-term evaluation of the deforestation outcomes to analyze whether the adoption of alternative livelihood activities was a causal mechanism for self-sustaining the deforestation reduction induced by a REDD+ initiative. We hypothesized the REDD+ initiative promoted heterogeneous outcomes in the long-term, which varied according to whether households adopted alternative livelihood activities. Indeed, treated households that adopted new activities had an average of 14.67% to 16.90% more forest than controls, while null impacts were observed in treated households that did not adopt alternative livelihood activities. In the third chapter, we assessed both short and long-term effects of the initiative on farm income and agricultural productivity. We also investigated if increases in agricultural productivity may have contributed to forest conservation (land sparing) or to forest loss (rebound effect). Results indicate null impacts on farm income and agricultural productivity in the early project stage. Yet, in the long-term, higher farm income and yields per hectare were detected. We found no sufficient evidence neither for the rebound effect nor for land sparing. On aggregate, our findings indicate the REDD+ initiative left win-win outcomes in terms of forest conservation and increasing agricultural profitability. Notably, the main REDD+ implications to conservation of our findings are: i) temporary payments might effectively delay, though not permanently eradicate forest loss; ii) adoption of alternative livelihoods may ensure self-sustained deforestation reduction.